Dietary factors and sociodemographic determinants of non-communicable diseases among adults: evidence from a cross-sectional study - Mohieldin, Ali (Frontiers in Public Health, 2025)
BackgroundNon-communicable diseases (NCDS) account for over 70% of global mortality. Integrated data on lifestyle and dietary risk factors remain limited in the middle east.ObjectiveTo assess associations between sociodemographic, anthropometric, and dietary predictors and self-reported NCD status among adults in Saudi Arabia.MethodsA cross-sectional survey of 430 adults in Asir region province (July 2025) collected data on demographics, BMII, physical activity, and dietary intake across 10 food groups. NCDs were defined as physician-diagnosed cardiovascular disease, diabetes mellitus type 2, cancer, or chronic respiratory illness. Bivariate associations were evaluated using pearson’s χ2 tests; multivariable logistic regression identified independent predictors. IBM SPSS v29 was used.ResultsNCD prevalence was 49.3%. Bivariate analysis showed age (p < 0.001), female gender (p = 0.045), marital status (p = 0.034), obesity (p < 0.001), and occupation (p = 0.004) were significant predictors. Low fruit (p = 0.033), dairy (p = 0.002), and grain intake (p = 0.014), and high sugary food intake (p = 0.009) were significantly associated with NCDs. Logistic regression indicated that female gender (OR = 2.87, 95% CI: 1.02–8.08), low dairy intake (OR = 0.21, 95% CI: 0.08–0.57), high sugar intake (OR = 0.10, 95% CI: 0.03–0.33), and smoking (OR = 0.35, 95% CI: 0.13–0.93) were significant independent predictors. Some findings were counterintuitive, warranting cautious interpretation.ConclusionNearly half of adults had at least one NCD. Modifiable dietary factors, notably fruit, dairy, grain, and sugar intake, emerged as key risk factors. Tailored dietary interventions are crucial.